The statistical politics of exceptional territories. (March 2017) - Uitermark, Justus; Hochstenbach, Cody; van Gent, Wouter
Abstract: The so-called Rotterdam Act enables municipal governments in the Netherlands to bar poor households with no or limited residential history in the metropolitan area from moving into certain neighborhoods. Although evidently at odds with principles of equality enshrined in law, the Act has emerged as a standard part of the policy tool kit. This article seeks to explain how the Rotterdam Act came to pass. Asking this question sets us on the path of reconstructing how specific urban areas suffering from extraordinary problems were identified and how using exceptional measures to exclude specific groups were instituted. In a word, we are interested in the construction of exceptionality. We show that the construction of exceptional territories is based on the interplay of discretionary power and statistical calculation. We discuss the wider relevance of our analysis to the emerging field of critical data studies and for understanding the links between sovereignty, territory and statistics in constitutional democracies.